The Role of Far-Right Networks in the Cultural War and International Relations in Europe - Joel Ivan Gonzalez Cedillo (Вестник Кемеровского государственного университета. Серия: политические, социологические и экономические науки)
The author analyzes the internationalization of European far right civil societies as non-traditional political actors that engage in international relations creating ideological networks. The purpose of the article is to reveal the role of European fascist civil societies in international ideological activism as a response to a perceived cultural war against globalism and cultural Marxism of left internationalists. The article analyzes and comprehensively defines the issue of the cultural war in the West and describes the characteristics of Spanish fascist civil societies as non-traditional political actors exposing their perspective as cultural war revolutionaries. Attempts to create international far right networks by Spanish actors are studied based on the analysis of The Militant – The Cultural War, the manifesto published by the Spanish fascist civil society European Future in February 2023. A discourse analysis of this document exposes the ideological narratives of this group that can help to create a theoretical framework of the cultural war concept for European far right politics. The results demonstrate that European far right activists consider there is an ideological war against Marxists and other leftist groups. Activists of the European Future see themselves as far right revolutionaries capable of causing an ideological revolution in European democracies. The manifesto serves as a tool to call out to other European far right activists of the continent to join them. The results can contribute to future research of ideological extremism and European far right activism.